The impact of the COVID-19 pandemic on diet, fitness, and sedentary behaviour of elite para-athletes - Shaw, A.; Bertrand, L.; Deprez, D.; Ko, J.; Zello, G. A.; Chilibeck, P. D. (Disability and Health Journal, 2021)
Background: With the declaration of the COVID-19 pandemic the 2020 Paralympic Games were postponed, impacting the athletes` competition schedule for the year. Due to the interrupted competition schedule and potentially decreased motivation, Paralympic athletes may be at risk for a highly disrupted training schedule, impacting their ability to prepare for the 2021 Games.